2014
DOI: 10.1603/en13107
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Genomic and Proteomic Approaches to Characterize the Symbiotic Population of the Banana Aphid (Hemiptera: Aphididae)

Abstract: Aphids are known to live in symbiosis with specific bacteria called endosymbionts that have positive or negative impacts on their hosts. In this study, six banana aphid (Pentalonia nigronervosa Coquerel) strains from various geographical origins (Gabon, Madagascar, and Burundi) were screened to determine their symbiotic content, using complementary genomic (16S rDNA sequencing and specific polymerase chain reaction) and proteomic (two-dimensional difference gel electrophoresis coupled with protein identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 67 publications
4
19
0
Order By: Relevance
“…The most frequently detected facultative endosymbionts of aphids are Hamiltonella defensa, Regiella insecticola, S. symbiotica, Rickettsia sp., Ricketsiella sp., Spiroplasma sp., the Pea Aphid X-type Symbiont (PAXS) and Wolbachia sp. (Sandström et al, 2001;Oliver et al, 2003;Oliver et al, 2006;Degnan & Moran, 2008b;Guay et al, 2009;Oliver et al, 2010;Tsuchida et al, 2010;Łukasik et al, 2013b;De Clerck et al, 2014). A concise review of endosymbiont occurrence in aphid populations (Zytynska & Weisser, 2016) found that the facultative endosymbionts S. symbiotica and Wolbachia infected the highest proportion of the aphid species assessed (47% and 43%, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently detected facultative endosymbionts of aphids are Hamiltonella defensa, Regiella insecticola, S. symbiotica, Rickettsia sp., Ricketsiella sp., Spiroplasma sp., the Pea Aphid X-type Symbiont (PAXS) and Wolbachia sp. (Sandström et al, 2001;Oliver et al, 2003;Oliver et al, 2006;Degnan & Moran, 2008b;Guay et al, 2009;Oliver et al, 2010;Tsuchida et al, 2010;Łukasik et al, 2013b;De Clerck et al, 2014). A concise review of endosymbiont occurrence in aphid populations (Zytynska & Weisser, 2016) found that the facultative endosymbionts S. symbiotica and Wolbachia infected the highest proportion of the aphid species assessed (47% and 43%, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Recent in situ hybridization studies revealed that Wolbachia and Buchnera coexist in host bacteriocytes (G omez-Valero et al, 2004;De Clerck et al, 2014) and they can cooperate to supply essential nutrients to the host (De Clerck et al, 2014). Although it is unclear where Wolbachia resides in T. macrotuberculatus, its detection in almost all of the aphids examined implies that Wolbachia-infected aphids may have advantageous characteristics to dominate in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Buchnera, Wolbachia sp. (an a-proteobacterium) has been found in some aphid species (G omez-Valero et al, 2004;Wang et al, 2009;Augustinos et al, 2011;De Clerck et al, 2014). The roles of Wolbachia in hosts range from parasitism to mutualism.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, P. nigronervosa is the primary vector of the Banana bunchy top virus (BBTV), the most severe viral disease of banana worldwide (Dale 1987). P. nigronervosa carries at least two bacterial symbionts: Buchnera aphidicola and Wolbachia (de Clerck et al 2014). Buchnera aphidicola is an obligate (primary) symbiont present in almost all aphid species and provides essential amino acids to the aphids (Baumann 1995;Douglas 1998;Hansen and Moran 2011;Shigenobu and Wilson 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Wolbachia is considered a facultative (secondary) symbiont and is found in a few aphid species at low abundance (Augustinos et al 2011;Jones et al 2011). Interestingly, Wolbachia is found systematically across the P. nigronervosa range (de Clerck et al 2014) and is also present in the closely related species P. caladii van der Goot (Jones et al 2011), which rarely colonizes banana, and prefers other plant species of the order Zingiberales (Foottit et al 2010).…”
Section: Introductionmentioning
confidence: 99%